Dynamic Change of Aroma Components in Chimonanthus praecox Flower Scented Teas During Absorption and Storage - Xiongyuan Si; Hao Zuo; Penghui Li; Ye Tan; Mangmang Tan; Zhihui Chen; Changsong Chen; Taolin Chen; Zhonghua Liu; Jian Zhao (Foods)
Flower-scented teas become increasingly popular to new generations, due to their infused floral essences of diverse volatile compounds and additional health functions. Flower-scented teas have significantly broadened the spectrum of aroma perception, intensity, and longevity. Here, Chimonanthus praecox flowers were used to scent tea dhools to create different Chimonanthus teas with strong and characteristic aromas. The dynamic absorption of aromas by three tea dhools, and aroma compatibility in three flower-scented teas, and the aroma retention in Chimonanthus teas during storage were investigated. At least twelve aroma compounds were selectively absorbed by three tea dhools, with seven compounds, pulegone, 3-phenylpropanol, (E)-cinnamaldehyde, cinnamyl alcohol, γ-phenylpropyl acetate, (E)-isoeugenol, and (E)-cinnamyl acetate, commonly absorbed to three Chimonanthus teas. The different absorption preferences to floral volatiles and absorption capacity of three tea dhools could be related to their surface structures and trichome conditions. Linalool, phenylmethyl acetate, and methyl salicylate as significant volatile components were substantially enhanced for both Chimonanthus flowers and tea dhools, thereby augmenting the floral bouquet of Chimonanthus tea. After 56 days of storage, alcohol volatiles emerged as the predominant volatile types, although esters are the major contributors to the aroma of freshly prepared Chimonanthus teas.